Pengaruh Motivasi dan Komunikasi Terhadap Kinerja Karyawan Pada PT Valco Indoasiatec - Linda Rubiani; Mayesti Mayesti (Komunitas Dosen Indonesia, 2022)
This study purpose are determine effect of motivation and communication on employee performance at PT Valco Indoasiatec by using this 115 response sample random sampling techniques. The data’s collections methods using a questionnaire. Hypothesis testing using the t test shows that motivation and communication have significant effect on employee performance. Then through the F test, motivation and communication simultaneously affect the employee performance